Health risk assessment of heavy metals in irrigated fruits and vegetables cultivated in selected farms around Kaduna metropolis, Nigeria. Issue 1 (1st January 2021) - Lere, Bahiyya Kabir; Basira, Ibrahim; Abdulkadir, Saidu; Tahir, Salisu Muhammad; Ari, Hadiza Abdullahi; Ugya, Adamu Yunusa
ABSTRACT: This study assessed heavy metals levels in water, soil, fruits (banana, pawpaw) and vegetables (cucumber, cabbage and garden egg) from Bashama, Danmani and Danbushiya farms within Kaduna metropolis, Nigeria. A total of 63 samples (water (9), soil (9), fruits and vegetables (45)) were randomly collected, processed and analyzed for heavy metals using a microwave plasma atomic emission spectrometer. The heavy metal concentration in soil was found to be highest for Fe (57.30–63.51) mg/kg and the least was observed for Cu (0.45–1.45) mg/kg. High levels of Pb (0.02–0.03) mg/l, Cd (0.07–0.1) mg/l and Fe (3.23–3.42) mg/l were determined in the irrigation water exceeding the World Health Organization (WHO) standard. Some of the heavy metals (Fe, Zn and Cu) found in the various fruits and vegetables were essentials metals. Toxic metals like Pb and Cd were also present with concentrations above the World Health Organization permissible limit of 0.2 and 0.1, respectively. In the fruits and vegetables examined, the average mean concentration of metals showed significant variations with Fe having highest concentration of (7.82 mg/kg) in most of the samples from the farms. Health risk assessment of heavy metals from the fruit and vegetable samples indicated that all metals are within hazard quotient limit of less than 1 except for Cd, while for the hazard index, all the metals surpass limit of 1 which showed that the samples are likely to be of health concern. For permissible maximum tolerable daily intake in the metals studied, Cd has the highest concentration. The activities around these farms play a significant role in elevating the concentration of Cd and Pb in the fruits and vegetables a little above the WHO set standard of 0.3 mg/kg and 0.2 mg/kg, respectively. Measures to reduce the concentration of heavy metals in fruits and vegetables should be carried out in further works to avoid their health risk in human.